Tuition Fees, as User Prices, and Private Incentives - George Economides; Apostolis Philippopoulos; Stelios Sakkas (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies the aggregate and distributional implications of introducing tuition fees for public education services into a tax system with income and consumption taxes. The setup is a neoclassical growth model where agents differ in capital holdings. We show that the introduction of tuition fees (a) improves individual incentives to work and/or save and (b) can be both efficient and equitable. The focus is on the role of tuition fees as an extra price and how this affects private incentives.
Keywords: H40; H20; D60; 330; user prices; tax mix; efficiency; equity